Implementasi Metode Komunikasi Total Pada Siswa Tunarungu Di SLB Negeri Keleyan - Ryn, Amira; Nova Estu Harsiwi (Journal of Special Education Lectura, 2024)
This study highlights the importance of implementing the total communication method at SLB Negeri Keleyan in supporting the communication development and learning of deaf students. The research aims to analyze the implementation of the total communication method at SLB Negeri Keleyan, involving various communication aids and the entire school community. The qualitative research method with a descriptive approach was used, involving interviews, observations, and documentation. The subjects of the study were 5 deaf students aged 8-15 years. The results show that the total communication method, which combines verbal aspects, facial expressions, and hand signals, activates various sensory channels such as vision, hearing, touch, and body movement. The implementation of total communication at SLB Negeri Keleyan involves several key steps such as lip reading, the oral-aural method, and manual total communication. The application of this method shows that deaf students can communicate effectively not only within the school environment but also in daily interactions. They feel comfortable using total communication, demonstrating improvements in social skills, self-confidence, and interaction abilities.